The contribution of smallholder irrigation farming to rural livelihoods and the determinants of benefit distribution : the case of Limpopo Province of South Africa - Machethe, Charles Lepepeule (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.